BUILDING A POLICY FOR COMBATING CRIMINAL ACTS OF TERRORISM THROUGH THE DEATH PENALTY - fajar purwawidada (Universitas 17 Agustus 1945 Semarang, 2021)
Terrorism is an extraordinary crime that can cause an atmosphere of terror, widespread fear, and mass casualties for the community. The government makes policies to counter terrorism through Law no. 15 of 2003 concerning the Eradication of Criminal Acts of Terrorism, amended by Law no. 5 of 2018. The law provides for the death penalty for perpetrators of terrorism crimes. Nevertheless, the reality is that acts of terror in Indonesia are still happening and are increasing. The problem raised in this study is how to reconstruct the policy of countering terrorism through the death penalty. This legal research is normative juridical research with an empirical juridical approach. The types of data used include primary data and secondary data. Data collection techniques using documentary studies as secondary data and supported by primary data using the interview method. The analysis used is qualitative normative data analysis. Based on this research, the results show that terrorism crimes are committed by groups that are generally political victims; injustice, inequality, poverty, discrimination. The goal is to fight a mighty force that is impossible to fight openly. Implementing the death penalty for terrorism crimes does not provide a deterrent effect for perpetrators of terror acts in Indonesia. This happens because the lack of understanding of the characteristics of terrorism crimes and harsh actions actually lead to new, greater violence. The solution to this problem is to change the legal approach towards a sociological, persuasive and deradicalization approach